O Porto patriota e liberal em Whispering (1995) e Caterina (1999), de Jane Aiken Hodge (1917-2009) - Alarcão, Miguel (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
In 2007, within the framework of the bicentennial commemorations of the Peninsular War on Portuguese soil, we presented the novel The Winding Stair (1968), by Jane Aiken Hodge, a prolific Anglo-American authoress, although largely unknown among us; at the time, we were also seeking to correlate The Winding Stair with the accounts and images, often prejudiced and stereotyped, conveyed by travel literature/writing. However, Jane Hodge has authored over thirty novels, two of which bound to be of interest to Anglo-Portuguese literary and cultural studies: Whispering (1995), set in Oporto at the time of the Peninsular War, and its sequel, Caterina (1999), during the Portuguese liberal and civil wars. This article is therefore dedicated to them both.